MENGGALI MAKNA TAKUT AKAN TUHAN DALAM KEHIDUPAN ORANG PERCAYA DI MASA KENORMALAN BARU - Irene Tangke Layuk; Sri Susanti Taruk, Widya Mian Roro', Juliani Pamele, Irma Paseru (ADISAM PUBLISHER, 2025)
This article aims to explore the meaning of fear of God in the lives of believers, particularly in the context of the post-pandemic new normal. Fear of God is a central theological concept in the Bible that is often misunderstood as a negative fear. However, in biblical understanding, fear of God reflects an attitude of respect, obedience, and awareness of God's presence and holiness, which encourages people to live in wisdom and integrity. Through a qualitative approach based on literature, this article explores theological understanding of biblical texts, analyzes the dimensions of spirituality born of fear of God, and examines its relevance in facing spiritual, social, and moral challenges in the new normal. Furthermore, this article highlights the crucial role of faith education in shaping Christian character rooted in fear of God. The study's findings indicate that this attitude is not only crucial as a foundation for personal faith but also as a transformative force that shapes authentic, resilient, and contextual Christian lives. Therefore, the value of fear of God needs to be continuously instilled deeply through holistic faith education integrated into the lives of communities of believers